Synthesis and Characterization of Some New Spirothiadiazole Oxindoles and their Mannich Bases - Sim, Kooi-Mow; Leong, Pei-Theng; Wong, Wai-Sum; Teo, Kah-Cheng (Letters in Organic Chemistry, 2022)
A series of new spirothiadiazole oxindoles were synthesized by the reaction of 4-amino-5- mercapto-3-[(1H-indol-3-yl)methyl]-1,2,4-triazole and isatin derivatives. The reaction of spiro [indole] thiadiazoles with formaldehyde and piperidine afforded the corresponding Mannich bases. The structures of newly synthesized compounds were characterized by IR, 1D-NMR, 2D-NMR, and LC/MS spectral data.
Keywords: 4-triazole